Proposal to Reduce Working Hours for Employees in Organizations/Enterprises (Private Sector) in Vietnam – Towards Conformity with International Labor Treaties - Đức, Lê Văn (International Journal of Innovative Research and Scientific Studies, 2025)
According to a survey by the International Labor Organization (ILO), Vietnam is among the countries with high working hours in the region and in the world, while reducing working hours is a common trend in many countries and a progressive trend in society. On that basis, this study focuses on theoretical issues, assessing the implementation of policies and legal regulations on working hours for employees in Vietnam and around the world. From there, recommendations are proposed for the early implementation of reduced working hours for employees in organizations/enterprises (private sector) in Vietnam. The study uses synthesis and analysis methods based on the theoretical basis of the Party's policies and guidelines, the State's laws in Vietnam, international labor treaties, and qualitative methods through the synthesis and analysis of relevant documents. The results of the study are as follows: (1) The theoretical basis system of regulations on working hours in Vietnam and regulations of international law on working hours for workers globally; experiences of countries in the world on reducing working hours and experimenting with a 4-day workweek for workers; (2) Assessment of the current situation of working hours for workers in organizations/enterprises (private sector) in Vietnam. Thereby, the author proposes to reduce the normal working hours per week for workers in organizations/enterprises (private sector) from 48 hours/week to 44 hours/week, aiming for 40 hours/week and not increasing the maximum overtime hours so that workers can maintain their health, regenerate their labor, have time to take care of their families, and improve the quality of work and life.